Non-Financial Policy Disclosure by Polish Listed Companies: The Impact of Directive 2014/95/EU - Ewa RÓŻAŃSKA; Łukasz MATUSZAK (Communications of International Proceedings, 2021)
Purpose: The purpose of this study is to investigate both the extent of non-financial policy disclosure and its determinants that refer to regulatory changes as well as to skills and competencies of companies in sustainability reporting. Design/methodology/approach: The sample comprised 71 selected Polish listed companies subject to the Directive 2014/95/EU over 6 years. Content analysis was used to measure the extent of policy-related disclosure. The econometric model was estimated using panel fixed effects. Findings: The extent of non-financial policy disclosure is significantly better than before the implementation of the Directive. Furthermore, we found that the Directive enforcement, company experience in sustainability reporting and company membership in a risky industry are significant determinants of non-financial policy-related disclosure. Originality: Our study enriches the literature on non-financial disclosure by providing self-constructed non-financial policy disclosure index based on requirements of the Directive 2014/95/EU. It also contributes to the understanding of the role of relevant variables in non-financial policy-related disclosure in voluntary and mandatory context.
Keywords: non-financial policy disclosure; ESG-related policy disclosure; sustainability policy disclosure; environmental policy disclosure; social policy disclosure; Directive 2014/95/EU